2010
DOI: 10.1016/j.jacc.2010.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Mechanistic Issues in Early Repolarization

Abstract: Early repolarization, involving ST-segment elevation and, sometimes, prominent J waves at the QRS-ST junction, has been considered a normal electrocardiographic variant for over 60 years. A growing number of case reports and case-control studies indicate that in some instances, early repolarization patterns are associated with increased risk of idiopathic ventricular fibrillation. Epidemiological evidence indicates a dose effect for the risk of cardiac and sudden death with the extent of J-point elevation. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 73 publications
2
29
0
5
Order By: Relevance
“…16,23,[33][34][35] Some controversy exists as to whether the electrocardiographic findings represent ER, late depolarization, or neither. 36,37 The repolarization hypothesis suggests that the presence of the ERP reflects regional heterogeneity in the dispersion gradient of myocardial refractoriness prompted by a net outward shift in repolarizing current.…”
Section: Biological Basis and Geneticsmentioning
confidence: 99%
“…16,23,[33][34][35] Some controversy exists as to whether the electrocardiographic findings represent ER, late depolarization, or neither. 36,37 The repolarization hypothesis suggests that the presence of the ERP reflects regional heterogeneity in the dispersion gradient of myocardial refractoriness prompted by a net outward shift in repolarizing current.…”
Section: Biological Basis and Geneticsmentioning
confidence: 99%
“…Such a pattern in the anterior precordial leads (V 1 to V 3 ) was excluded from the studies as it could occur in disease states such as Brugada syndrome and arrhythmogenic right ventricular cardiomyopathy/dysplasia. Further, early repolarization pattern in the anterior precordial leads is considered to have a benign prognosis (116). Recent data suggest the KCNJ8 gene may be involved in early repolarization syndrome (117).…”
Section: Idiopathic Ventricular Fibrillationmentioning
confidence: 99%
“…Recent data suggest the KCNJ8 gene may be involved in early repolarization syndrome (117). Early repolarization pattern is not uncommon and has for years been considered a normal ECG variant with a benign prognosis (116). The mechanism of VT or VF that can occur with it is not well understood (116).…”
Section: Idiopathic Ventricular Fibrillationmentioning
confidence: 99%
“…β-adrenergic activation with isoproterenol is effective in suppressing ER arrhythmias by enhancing inward calcium current (Figures 2 and 5). 53 Quinidine via its effects to inhibit I to is effective as well. 53 A multicenter observational cohort study has demonstrated that isoproterenol in acute cases and quinidine in chronic cases is effective for suppression of VF related to ERS.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…53 Quinidine via its effects to inhibit I to is effective as well. 53 A multicenter observational cohort study has demonstrated that isoproterenol in acute cases and quinidine in chronic cases is effective for suppression of VF related to ERS. 54 In this study (n=122; 90 male patients; mean age, 37±12 years), patients with ER in the inferolateral leads with >3 episodes of idiopathic VF (including those with electrical storms) had empirical antiarrhythmic drug therapy prescribed by the treating physicians.…”
Section: Therapeutic Strategiesmentioning
confidence: 99%